Constitutionalism as A Design For Limiting Power in The Era of Post-Truth Democracy - Martitah Martitah; Arif Hidayat; Moh. Imam Gusthomi; Niken Septiani; Tegar Islami Putra; Rahmawati Mohd Yusoff (Indonesian State Law Review (ISLRev), 2025)
The principle of constitutionalism is the main pillar in maintaining the balance of power and upholding the rule of law in a democratic system of government. In the Indonesian context, the dynamics of state administration show that this principle is increasingly relevant, especially amid the trend of widening executive and legislative powers and the challenges of the post-truth era of democracy. This research uses a descriptive qualitative method with a literature study approach, reviewing various literature and research results from 2020 to 2025 to understand the urgency, implementation, and challenges of constitutionalism in limiting power in Indonesia. The discussion begins with an elaboration on the nature of constitutionalism and its function in democracy, followed by an analysis of the mechanism for limiting power as a manifestation of constitutional principles, as well as the issue of term extension as an early symptom of the erosion of these principles. Furthermore, new challenges in the digital era involving the influence of technology and oligarchy in shifting the meaning of constitutionalism to mere formality are examined. The findings show that the weakening of the principle of constitutionalism does not only occur through normative violations, but also through political engineering of power hidden in the practice of procedural democracy. Thus, strengthening constitutionalism through legal reform, strict institutional control, and public political literacy is an urgent agenda in maintaining the integrity of a healthy and equitable democratic system.